2023
DOI: 10.1111/cts.13576
|View full text |Cite
|
Sign up to set email alerts
|

First‐in‐human phase 1 trial evaluating safety, pharmacokinetics, and pharmacodynamics of NLRP3 inflammasome inhibitor, GDC‐2394, in healthy volunteers

Fei Tang,
Rebecca Kunder,
Tom Chu
et al.

Abstract: Inappropriate and chronic activation of the cytosolic NOD‐, LRR‐, and pyrin domain‐containing 3 (NLRP3) inflammasome, a key component of innate immunity, likely underlies several inflammatory diseases, including coronary artery disease. This first‐in‐human phase I trial evaluated safety, pharmacokinetics (PKs), and pharmacodynamics (PDs) of oral, single (150–1800 mg) and multiple (300 or 900 mg twice daily for 7 days) ascending doses (SADs and MADs) of GDC‐2394, a small‐molecule inhibitor of NLRP3, versus plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Although this occurrence, observed at the highest tested dose and within a short time frame, might suggest a direct hepatotoxicity mechanism, the possibility of immune-mediated or other mechanisms contributing to this underlying idiosyncratic druginduced liver injury cannot be excluded. 77 Consequently, because of safety concerns, the project was terminated.…”
Section: Exploration Of 2-furan Isopropanol Moietymentioning
confidence: 99%
See 1 more Smart Citation
“…Although this occurrence, observed at the highest tested dose and within a short time frame, might suggest a direct hepatotoxicity mechanism, the possibility of immune-mediated or other mechanisms contributing to this underlying idiosyncratic druginduced liver injury cannot be excluded. 77 Consequently, because of safety concerns, the project was terminated.…”
Section: Exploration Of 2-furan Isopropanol Moietymentioning
confidence: 99%
“…However, during the investigation of drug–drug interactions in the Phase I clinical trial by Genentech, two participants experienced a grade 4 drug-induced liver injury associated with the treatment. Although this occurrence, observed at the highest tested dose and within a short time frame, might suggest a direct hepatotoxicity mechanism, the possibility of immune-mediated or other mechanisms contributing to this underlying idiosyncratic drug-induced liver injury cannot be excluded . Consequently, because of safety concerns, the project was terminated.…”
Section: Structural Modification Based On the Compound Mcc950mentioning
confidence: 99%
“…In addition, IL-1β has been shown to play an important role in chronic diseases such as gout or type 2 diabetes as well as in neuroinflammatory disorders including multiple sclerosis, Alzheimer’s disease, or diabetic neuropathy. Moreover, the CANTOS study, a secondary risk prevention study in cardiovascular disease with the IL-1β monoclonal antibody canakinumab, has shown that IL-1β contributes to cardiovascular risk, lung cancer, and osteoarthritis. NLRP3, as the main inflammasome sensor for sterile danger signals associated with many of these diseases, has become an attractive therapeutic target for low-molecular-weight drug discovery, with the potential to inhibit IL-1β, IL-18, and pyroptosis, and penetrate tissues inaccessible to biologics . The publication of MCC950 (also known as CP-456,773 or CRID3), as a bona fide NLRP3 inhibitor, and the subsequent confirmation of its direct binding to the NLRP3 NACHT domain by biochemical methods and crystallography, have allowed for a first wave of MCC950 -derived NLRP3 inhibitors such as ZYIL1 , GDC-2394 , and NT-0796 (Figure ) to enter early clinical development. These compounds have potential liabilities, including liver toxicity, , so broader chemical diversity is needed to maximize chances of developing a safe and efficacious NLRP3 inhibitor. In this paper, we describe the discovery of tricyclic NLRP3 inhibitors which have been optimized from an initial screening hit to an advanced preclinical candidate.…”
Section: Introductionmentioning
confidence: 99%
“…21 The publication of MCC950 (also known as CP-456,773 or CRID3), 22 as a bona fide NLRP3 inhibitor, and the subsequent confirmation of its direct binding to the NLRP3 NACHT domain by biochemical methods 23 and crystallography, 24 have allowed for a first wave of MCC950derived NLRP3 inhibitors such as ZYIL1, GDC-2394, and NT-0796 (Figure 1) to enter early clinical development. 25−28 These compounds have potential liabilities, including liver toxicity, 29,30 so broader chemical diversity is needed to maximize chances of developing a safe and efficacious NLRP3 inhibitor. In this paper, we describe the discovery of Table 1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…32−35 One such candidate, GDC-2394, contained a sulfonylurea core as found in CP-456,773 and was also found to carry liver safety concerns when administered at a high dose to healthy volunteers. 32 However, other sulfonylurea-containing NLRP3 activation inhibitors have not reported similar liver safety issues in clinical trials, 33−35 and a mechanistic understanding of the root cause for the liver toxicity is unknown. Given this uncertainty, a better understanding of the degree of target suppression required to achieve biological benefit is needed to mitigate possible side effects resulting from excessive pathway inhibition and/or compound overexposure.…”
mentioning
confidence: 99%